International Environmental Law and Climate Change Adaptation in ASEAN Island Nations: An Analysis of Global and Regional Frameworks - Oli, Frediks (PERFECT EDUCATION FAIRY, 2025)
Climate change poses a profound threat to ASEAN island nations, including Indonesia, the Philippines, Brunei Darussalam, and Singapore. These countries are particularly vulnerable to rising sea levels, tropical storms, coastal ecosystem degradation, and biodiversity loss, requiring comprehensive legal and policy responses. This study adopts a normative legal approach to examine international environmental law instruments, such as the United Nations Framework Convention on Climate Change (UNFCCC), the Kyoto Protocol, and the Paris Agreement, alongside ASEAN regional frameworks, including the ASEAN Agreement on Disaster Management and Emergency Response (AADMER). Using statutory, conceptual, and comparative approaches, the research analyzes the extent to which international legal principles are integrated into national and regional adaptation policies. Findings indicate that principles such as the Common but Differentiated Responsibilities (CBDR) approach, the precautionary principle, and sustainable development have been incorporated, although implementation varies significantly across states. The Philippines demonstrates a strong disaster adaptation legal framework, while Indonesia struggles with interagency coordination. Brunei emphasises ecosystem conservation, and Singapore pursues technology-driven adaptation policies. At the regional level, ASEAN has introduced cooperative mechanisms; however, these largely remain in the realm of soft law, with limited enforcement power. The study emphasizes the need to strengthen regional legal instruments, align national policies with international frameworks, and increase access to international funding and technology.